Peer pressure : how can I say no? - Havelin, Kate, 1961- (Mankato, Minn. : LifeMatters, 2000)
Discusses different kinds of pressures exerted on young people by their peers, how these pressures can affect people, and ways to handle peer pressure
Includes bibliographical references and index
Keywords: Peer pressure -- Juvenile literature; Peer pressure in adolescence -- Juvenile literature; Peer pressure